Examining IT Service Management at Company XYZ through the Lens of ITIL V3 Service Operation Domain - Mutikno, Wiwit Gayuh Mugi; Rizaldi, Dani; Syanahieskara, Razel; Pratiwi, Widya Dian; Muntaqo, Firman; Aeni, Aisyah Nur; Jeenduang, Nutjaree (International Journal of Informatics and Information Systems, 2024)
The rapid development of information technology and good technology services is an expectation for all people, organisations, institutions, and universities in order to support activities, facilitate their activities and business processes. A business organisation needs to adapt to the current development of information technology. IT service management is a method of managing information technology systems that is centred on the consumer perspective of information technology services on the company's business. Company XYZ has implemented information technology that is intended for users to be able to carry out service management activities as well as processing company administrative data. Service Operation is a lifecycle phase that includes all the day-to-day operations of IT service management. Based on the results of research on 3 processes, namely Event Management, Request Fulfilment and Problem Management, it is necessary to increase the need for adequate hardware, software and infrastructure in meeting the needs of Company XYZ in working more effectively. Then the need for proper application of SOPs and modules to employees is somewhat more efficient in using information technology.